Evaluating the performance of asynchronous MAC protocols for wireless sensor networks. (5th September 2019) - Bengheni, Abdelmalek; Didi, Fedoua
In Wireless Sensor Networks (WSN), MAC protocols for duty-cycling can be classified into two categories: synchronous and asynchronous MAC protocols. Synchronous protocols make use of synchronised sleep-wake schedules to improve on data delivery rates. On the other hand, asynchronous protocols do not need to synchronise their sleep-wake schedules. The main objective of this paper is to evaluate the performance of an experimental WSN using two different asynchronous MAC protocol types; the first uses the preamble frame transmission such as B-MAC and X-MAC and the other type is based on beaconing paradigm that uses the beacon frame transmission as RI-MAC. In this experiment, we use OMNeT++/MiXiM network simulator to create WSN and then evaluate its performance in terms of the packet delivery ratio, mean latency and energy consumption. The simulation results show that RI-MAC performs better than X-MAC and B-MAC while the X-MAC is ranked second best before B-MAC.